Narrative Structures and Cultural Intersections: Exploring Malind Anim Folklore through Reader Responses - Anggawirya, Arin Mantara; Floriani, Rosalia (Elsya : Journal of English Language Studies, 2024)
This study is a literary research that used a reader-response approach, which can open insights into the reader's view of a literary work, to find the results of literary receptions in the Folklore of Malind Anim, an indigenous community that inhabits the southern Papua region. The study of the people's stories of the Malind-Anim community is still minimal, so this research is expected to trigger community’s enthusiasm to know the culture that is reflected in the People's Stories of the Society of Malind-Anim and also to be the material of policy-determining consideration in the efforts to preserve the stories of the people of the Anim. Questionnaires are given to 20 readers before reading Malind Anim's People's Stories, containing items that measure the level of readers, then they were invited for a semi-structured interview after reading to see the readers' response to the values in the people's stories of the Malind-Anim community. The research was divided into two phases. First, a structural approach to the work of People's Stories of Malind Anim society, where the researchers used heuristic and hermeneutic methods to find structure and literary elements. In the second phase, to investigate the implications of the work on the reader, the reader response approach was used to extract literary values from the reader's point of view. Results show readers at the developing level can only interpret values in general, such as religion, education, and the environment, and readers at the developed level can interpret that the folklore of the Malind Anim community has three main dimensions that readers can interpret at these levels: Environmental Protector, Gender Equality, and Mitigation.